CONSTRUCTION OF SELFDUAL EINSTEIN METRIC ON 4-DIMENSIONAL MANIFOLD - (NIM 10205024); Pembimbing: Dr. rer. nat. Bobby Eka Gunara, SUMARIO
Einstein manifold have shown a wide usage for many important topics in Riemannian geometry, for example: Riemannian submersions, homogeneous Riemannian spaces, Riemannian functionals and its critical point, Yang-Mills theory, 4-dimensional selfdual manifold, holonomy group, and quaternionic manifold [8]. In this paper, I construct selfdual Einstein metrics of nonzero scalar curvature with two commuting Killing fields, these metrics are called Calderbank-Pedersen metrics, to construct this metric we need some properties of selfdual spaces found by Joyce and some Einstein-Weyl spaces found by Ward so we shall discuss the relation of this construction to a class of selfdual spaces found by Joyce [3], and some Einstein-Weyl spaces found by Ward [6].